Understanding the Multidimensional Islamic Faith Through âAbd Al-GhanÄ« Al-NÄbulusÄ«âs Mystical Philosophy - Yamamoto, Naoki (Al-Jamiah Research Centre, 2013)
This paper tries to present a new perspective on Islamic faith and Muslim identity to Muslim minorities who are challenged in practicing or following Islamic law in non-Islamic countries or non-Muslims in the contemporary world. It will uncover the multidimensional perspective of the concept of faith based on sin (dhanb) and repentance (tawbah) through the mystical philosophy of a Syrian scholar, Abd al-GhanÄ« al-NÄbulusÄ« (d. 1143/1741) of the 18th century Ottoman Damascus who contributed to the field of Sufism particularly based on Ibn âArabÄ«âs thought of waá¸¥dat al-wujÅ«d (oneness of being) and insÄn kÄmil (the perfect man). NÄbulusÄ« believes that anyone who lived during the inexistence of prophetâs revelation, inhabited an isolated place cut off from information about Islam, or lived in dÄr al-á¸¥arb and did not make a hijra to dÄr al-islÄm could not be regarded as sinful in their deeds. However, faith in Allah is essential and infidelity is not forgiven regardless whether or not they live in dÄr al-islÄm or dÄr al-á¸¥arb. Further, NÄbulusÄ« insists that true faith can be achieved by understanding the sin of existence; the ignorance of the difference of existence between Allah and men.[Artikel ini menjelaskan identitas keberagamaan umat Islam minoritas yang dituntut untuk menerapkan syariat, namun harus hidup di negara non-muslim, dengan mendiskusikan perspektif multidimensional terhadap konsep dosa dan tobat khususnya konsep waá¸¥dat al-wujÅ«d dan insÄn kÄmil yang dikembangkan oleh Abd al-GhanÄ« al-NÄbulusÄ« (1143/1741), seorang sufi pemikir Syria yang hidup di masa kesultanan Usmani di Damaskus. NÄbulusÄ« berkeyakinan bahwa siapa saja yang hidup sebelum turunnya wahyu di masa Nabi, hidup di daerah terpencil yang tidak mengenal Islam, atau hidup di dÄr al-á¸¥arb dan tidak hijrah ke dÄr al-islÄm, tidaklah dibebani dosa atas perbuatannya. Namun demikian, iman kepada Allah amatlah penting dan kekufuran tidaklah dimaafkan, baik seseorang tersebut hidup di dÄr al-islÄm ataupun dÄr al-á¸¥arb. NÄbulusÄ« beranggapan bahwa iman yang hakiki bisa dicapai dengan memahami dosa eksistensial, yaitu mempersamakan eksistensi Allah dan manusia.]